2020
DOI: 10.1038/s41598-020-77700-z
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the coronavirus SARS-CoV-2: computational insights into the mechanism of action of the protease inhibitors lopinavir, ritonavir and nelfinavir

Abstract: Coronavirus SARS-CoV-2 is a recently discovered single-stranded RNA betacoronavirus, responsible for a severe respiratory disease known as coronavirus disease 2019, which is rapidly spreading. Chinese health authorities, as a response to the lack of an effective therapeutic strategy, started to investigate the use of lopinavir and ritonavir, previously optimized for the treatment and prevention of HIV/AIDS viral infection. Despite the clinical use of these two drugs, no information regarding their possible mec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
6

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 41 publications
1
27
0
6
Order By: Relevance
“…Likewise, inspection for these residues revealed that Hit1 targeted hotspot residues His41, Met49, Cys145, Met165, and Gln189, while Hit2 targeted residues His41, Met49, Cys145, His164, Met165, Glu166, and Gln189 characterized by various hydrogen, hydrophobic, and π-alkyl bonds (Figure 4 and Supplementary Table 2). Similarly, a previously established binding mode for Lopinavir and Ritonavir against 3CL pro was obtained during our analysis which provides support for the binding mode of identified Hit compounds (Bolcato et al, 2020;. Recently, a terpenoid (T3) from marine sponge Cacospongia mycofijiensis was also identified through in silico studies against SARS CoV-2 3CL pro showing similar binding interactions like our hit molecules (Sepay et al, 2021).…”
Section: Discussionsupporting
confidence: 84%
“…Likewise, inspection for these residues revealed that Hit1 targeted hotspot residues His41, Met49, Cys145, Met165, and Gln189, while Hit2 targeted residues His41, Met49, Cys145, His164, Met165, Glu166, and Gln189 characterized by various hydrogen, hydrophobic, and π-alkyl bonds (Figure 4 and Supplementary Table 2). Similarly, a previously established binding mode for Lopinavir and Ritonavir against 3CL pro was obtained during our analysis which provides support for the binding mode of identified Hit compounds (Bolcato et al, 2020;. Recently, a terpenoid (T3) from marine sponge Cacospongia mycofijiensis was also identified through in silico studies against SARS CoV-2 3CL pro showing similar binding interactions like our hit molecules (Sepay et al, 2021).…”
Section: Discussionsupporting
confidence: 84%
“…Although they were prescribed ad hoc to reduce SARS-CoV-2 infection, these drugs are no longer used, and they require further clinical evidences to be officially approved. Numerous computational studies showed that these two drugs interact rather well with SARS-CoV-2 M pro [ 50 , 51 ]. Unfortunately, their potency is still not sufficient to determine an adequate reduction of the infection.…”
Section: Sars-cov-2 M Pro Inhibitorsmentioning
confidence: 99%
“…Between working with monomeric or dimeric form for the MetaDy studies, we strategically chose the first one. In this regard, we found a precedent in the use of M pro monomers as drug targets, but with different approaches (Bolcato et al., 2020 ). The fact is that there is strong evidence that the active form of Mpros is dimeric, although a monomer-dimer equilibrium coexists (Xiong et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%